Sensitivity of crumb rubber particle sizes on electrical resistance of rubberised concrete. Issue 1 (31st December 2016) - Kaewunruen, Sakdirat; Meesit, Ratthaphong
Abstract: Railway track components often suffer from high aggressive loading and vibrating conditions of railway environment, causing high maintenance costs due to impact damage, rail seat abrasion and excessive noise and vibration to surrounding equipment. Thus, it is essential to have novel improvement of material capabilities in order to solve or reduce these problems. A nanoengineered improvement method for concrete material using crumb rubber has been recently introduced to railway applications. However, for modern electrified railway tracks, structural materials will need to provide electrical and signal insulation for effective operations of track circuits and electrification. This paper firstly highlights the importance of the particle sizes of crumb rubbers on the electrical resistivity of the concrete modified by crumbed rubbers. It shows that microscale crumb rubbers induce lesser electrical conduction capacity than nanoscale crumb rubber.